W- rich mixed oxide solid solutions under pressure; Journal of Physics: Conference Series; Vol. 1611 : Prospects of Fundamental Sciences Development (PFSD-2020) - Petrushina M. Yu.; Dedova E. S. Elena Sergeevna; Yusenko K. V.; Portnyagin A. S.; Papynov E. K.; Filatov E. Yu.; Korenev S. V.; Gubanov A. I. (2020, 2020)
Title screen